DEVELOPMENT OF STUDENTS’ INDIVIDUALITY DURING COVID-19 PANDEMIC: THE IMPACT OF DISTANT AND ONLINE EDUCATION - Nesyna, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
This article focuses on the problem of students' individuality developing as an important part of human individuality in the process of distance and online education during Covid-19 Pandemic. The theoretical basis is O. Grebenyuk’s individuality concept. In it, the individuality is defined as the unity of seven spheres, including intellectual, motivational, emotional, volitional, practical and subject-oriented, self-regulative and existential ones which are characterized the originality and uniqueness of a person. Positive students' individuality developing affects success of higher education and professional activity in medicine. This study adresses three key issues. First, it looks at the problem of students' individuality developing in the process of distance and online education during Covid-19 Pandemic. Second, it turns to examine dynamics of students' individuality spheres and components during one semester of professional training at the university. Finally, the paper considers gender differences in dynamics of students' individuality. The data for this study were collected using the questionnaire “The Technique of Student’s Individuality” by T. Grebenyuk. Eighty-five students were recruited for this research. The participants study at Immanuel Kant Baltic Federal University, they are future health professionals. The results suggest that in the process of distance and on-line education during Covid-19 Pandemic, positive dynamics in the development of all individuality spheres of medical students is revealed, especially in the motivational and intellectual spheres. The dynamics of all individuality spheres have differences in the male group of medical students except the existential sphere. But this problem needs deeper research.